2020
DOI: 10.1016/j.jbusres.2018.01.059
|View full text |Cite
|
Sign up to set email alerts
|

Measuring customer based place brand equity (CBPBE) from a public diplomacy perspective: Evidence from West Bengal

Abstract: A glaring paucity of a measuring instrument for place branding effectiveness and place brand equity still remains. This study contributes theoretically by exploring and developing the dimensions and instrument of customer based place brand equity (CBPBE) quantitatively, in the context of international relations (public diplomacy) between two places, West Bengal (in India) and Bangladesh. To this end, the study employed: focus group discussion, depth interviews and survey, in order to develop and validate the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 66 publications
(84 reference statements)
1
40
0
Order By: Relevance
“…One group comprised eight young respondents (aged 18-35 years), while the other contained eight participants between 36-55 years. This research refers to the approach of examining a diverse group of respondents proposed by Bose et al (2018) in their research on customer-based place brand equity. The respondents were required to describe their perceptions of green brands and their own experiences related to green brand relationship interactions.…”
Section: Item Generationmentioning
confidence: 99%
“…One group comprised eight young respondents (aged 18-35 years), while the other contained eight participants between 36-55 years. This research refers to the approach of examining a diverse group of respondents proposed by Bose et al (2018) in their research on customer-based place brand equity. The respondents were required to describe their perceptions of green brands and their own experiences related to green brand relationship interactions.…”
Section: Item Generationmentioning
confidence: 99%
“…Regarding the examination of the responses of the first question of the interview script, most of the interviewees confirmed that the conceptualization of CBE is a complex (Chatzipanagiotou et al, 2016;Zenker, 2014) yet current and rewarding topic (Bose et al, 2020;Pappu & Quester, 2010;Zeugner-Roth et al, 2008). For this sample of authorities, Aaker's CBBE model (1991) and Keller's concepts (1993Keller's concepts ( , 1998 prevail in the brand equity literature and should be adjusted or tested through their application to studies regarding place brand equity.…”
Section: The Conceptualization Of Country Brand Equitymentioning
confidence: 80%
“…Additionally, Keller argued that brand associations "may be created by linking the brand to another node or information in memory that conveys meaning to consumers" (1998, p. 74). Furthermore, place brand associations can influence brand image favorability when related to place brand equity (Bose et al, 2020;Zenker, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Destination branding -India Kamat (2010) describes the Goa tourism industry as a good place to visit but marketers should introduce new forms of tourism, except beach-centric tourism, to retain and attract potential tourists such as village tourism. Bose et al (2018) explore the customer-based place brand equity (CBPBE) quantitatively, in the context of international relations (public diplomacy) between two places, West Bengal (in India) and Bangladesh and suggests that brand salience and perceived quality dimensions are important for brand engagement of a place and brand loyalty from the point of view of investment. Venkatachalam and Venkateswaran (2010) suggest that the success of countries such as Australia, France and Italy shows that destination can become brands that are contemporary and timeless.…”
Section: Asia-based Brand Equitymentioning
confidence: 99%